Dynamic interactions of energy trade, logistics, and exchange rates in Indonesia - Baroleh, Zefanya Fernando; Chandra, Vionalisa (Jurnal Ekonomi Indonesia, 2026)
This study examines how global coal prices, international logistics costs, and exchange rate fluctuations jointly influence Indonesia’s coal export performance. Previous research has treated these factors separately, leaving a gap in understanding their interdependencies. Using monthly data from July 2015 to June 2025 (120 observations; effective sample = 119), this study applies the Vector Error Correction Model (VECM) with an optimal lag of one to capture both long- and short-run dynamics among coal exports, the Baltic Dry Index (BDI), coal prices, and the Rupiah/US Dollar exchange rate. The Johansen test identifies two cointegration relationships, confirming the presence of long-run equilibrium. Results show coal exports adjust rapidly to disequilibria, while coal prices and the BDI act as stabilizing variables. By contrast, the exchange rate does not significantly contribute to long-run correction, reflecting its dependence on domestic macroeconomic conditions. These findings imply Indonesia’s coal trade system is highly sensitive to external shocks yet supported by structural correction mechanisms. Policy implications highlight three priorities: reducing logistics costs through port modernization and customs reform, accelerating downstream processing to strengthen value addition, and diversifying export markets to mitigate external vulnerabilities. Together, these measures provide foundation for sustaining competitiveness in global energy trade.